2018
DOI: 10.21608/mjcu.2018.59622
|View full text |Cite
|
Sign up to set email alerts
|

Serum Neutrophil Gelatinase-Associated Lipocalin as a Biomarker for Early Renal Dysfunction in Adult Egyptian Patients with b-Thalassemia Major

Abstract: Background: Renal dysfunction in thalassemia may occur before the occurrence of any symptoms, Induction of NGAL after kidney injury precedes the elevation of classical markers for kidney damage, which made it a promising marker for renal dysfunction in β -thalassemia, major.Aim of the Work: To assess value of serum NGAL in patients with β -thalassemia major as an early marker of renal impairment. Patients and Methods:The present study enrolled 70 subjects and they were classified into two main groups: • Group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 3 publications
0
0
0
Order By: Relevance
“…Recent studies have revealed that there are different tubular and glomerular abnormalities in patients with b-TM major and that renal dysfunction may occur in such patients without any clinical symptoms [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have revealed that there are different tubular and glomerular abnormalities in patients with b-TM major and that renal dysfunction may occur in such patients without any clinical symptoms [5].…”
mentioning
confidence: 99%
“…So, there is an urgent need for early predictive biomarkers of renal impairment in b-TM major as early intervention can significantly improve the prognosis [7].…”
mentioning
confidence: 99%